Contemporary economics - McEachern, William A. (Thomson South-Western, 2005)
Provides a coverage of fundamental economic topics, concentrating on the NCEE standards. This book provides explanations of demand, supply, market equilibrium, decision making, market institutions, the national economy, government's role, public policy, and the international economy. It incorporates print, video, electronic, and online resources.